OP IX – 4 Quantification of environmental burden of disease related to nitrogen dioxide exposure in germany. (18th March 2018) - Kraus, Ute; Schneider, Alexandra; Breitner, Susanne; Cyrys, Josef; Tobollik, Myriam; Plaß, Dietrich; Wintermeyer, Dirk; Diegmann, Volker; Peters, Annette
Abstract : Background/aim: Epidemiological studies have shown associations of nitrogen dioxide (NO2 ) with numerous health outcomes. EU-wide air quality limit values for NO2 are in place but regularly exceeded at measuring stations near roads in Germany. Therefore, a health risk assessment for the NO2 -exposure of the German population was conducted. Methods: For 2007 up to 2014, maps of the annual spatial 1*1 km 2 distribution of a population-weighted NO2 concentration indicator were calculated based on assimilated modelling data of background NO2 within a 7*8 km 2 grid and population density within a 250*250 m 2 grid. For three model regions a small scale assessment of the NO2 exposure was achieved by considering concentrations in the higher resolved urban background as well as close to highly polluted street sections. A systematic literature search of epidemiological studies was performed to ascertain the current evidence on long-term health effects of NO2 and to identify exposure-response-functions transferrable to Germany. The Environmental Burden of Disease-concept was applied to quantify the NO2 -associated health risks for relevant outcomes. Results: The yearly mean of background NO2 slightly decreased from 13 μg/m 3 (range: 4.3 to 37.3 μg/m 3 ) in 2007 to 11.8 μg/m 3 (3.4 to 32.7 μg/m 3 ) in 2014. Using a counterfactual value of 10 µg/m 3, 5966 (95%-confidence interval: 2031 to 9, 893) premature deaths and 49, 726 (16, 929 to 82, 456) Years of Live Lost (YLL) due to cardiovascular mortality attributable to NO2 long-term exposure were estimated for the year 2014. Between 2007 and 2014 an overall slightly decreasing trend was observed for attributable premature deaths. The higher resolution of NO2 -concentration for the three model regions led to a substantial increase in the estimated number of premature deaths due to cardiovascular disease by 40% to 165%. Conclusion: The present estimates are based on NO2 concentrations reflecting background exposure and thus underestimate the burden of disease. A better accuracy of the NO2 exposure estimation accounting for the higher concentrations in urban areas close to traffic improves the burden of disease quantification and may enhance the distinction of health effects related to fine and ultrafine particles.